Kinematics. Part 1. Analysis of particle motion - Anischenko, G. O.; Lavinsky, D. V. (My University, 2023)
The book is devoted to the basics of theoretical mechanics in the section «Kinematics of a particle». Basic theoretical aspects, examples of solving common problems, as well as options for self-study work are presented. The book is intended for bachelor students studying in the specialties 131 «Applied mechanics» and 133 «Industrial Engineering».
Keywords: textbook; theoretical mechanics; velocity of a particle; acceleration of a particle; dynamics